Analisis Penyebab dan Dampak Adanya Sisa Lebih Perhitungan Anggaran (SiLPA) Pemerintah Kabupaten Bondowoso: (Analysis of Causes and Impacts of RemainingBudgetCalculations(SiLPA) of Bondowoso Regency Government) - Safira Solga Safitri; Kartika Aryanto; Andriana Andriana; Arnis Budi Santoso (UPT Penerbitan Universitas Jember, 2022)
The Regional Government is responsible for reporting on regional financial management with the aim of comparing the realization of revenue and expenditure with the predetermined budget so that the comparison is shown in the Remaining Budget Calculations (SiLPA). This research, uses descriptive quantitative methods to collect secondary data is in the form of documentation, while the primary data is in the form of interviews which are tested for validity by triangulation so that the discussion of this research uses qualitative purposes to determine the reasons for the deficit in the Bondowoso Regency government budget due to the SiLPA that must be absorbed. Other results show that the causes of SiLPA in the Bondowoso Regency government consist of exceeding revenues and the remaining expenditure budget and there is an impact of SiLPA on determining the next year's budget in the Bondowoso Regency government to cover the deficit and finance priority programs that have not been budgeted for in the initial APBD process that must be used in the following fiscal year as well as financing expenditures in order to channel the budget surplus according to its allotment.